# Misc 14 - Chapter 7 Class 12 Integrals

Last updated at April 16, 2024 by Teachoo

Miscellaneous

Misc 1
Important

Misc 2 Important

Misc 3 Important

Misc 4

Misc 5 Important

Misc 6

Misc 7 Important

Misc 8 Important

Misc 9

Misc 10 Important

Misc 11

Misc 12

Misc 13

Misc 14 Important You are here

Misc 15

Misc 16

Misc 17

Misc 18 Important

Misc 19 Important

Misc 20

Misc 21

Misc 22

Misc 23 Important

Misc 24 Important

Misc 25 Important

Misc 26 Important

Misc 27 Important

Misc 28

Misc 29 Important

Misc 30 Important

Misc 31 Important

Misc 32

Misc 33

Misc 34

Misc 35

Misc 36 Important

Misc 37

Misc 38 (MCQ) Important

Misc 39 (MCQ)

Misc 40 (MCQ)

Integration Formula Sheet - Chapter 41 Class 41 Formulas Important

Question 1 Important Deleted for CBSE Board 2025 Exams

Question 2 Important Deleted for CBSE Board 2025 Exams

Question 3 Important Deleted for CBSE Board 2025 Exams

Question 4 (MCQ) Important Deleted for CBSE Board 2025 Exams

Chapter 7 Class 12 Integrals

Serial order wise

Last updated at April 16, 2024 by Teachoo

Misc 14 Integrate the function 1/((π₯^2 + 1)(π₯^2 + 4) ) Integrating 1/(π₯^2 + 1)(π₯^2 + 4) Let π₯^2=π¦ 1/(π₯^2 + 1)(π₯^2 + 4) =1/(π¦ + 4)(π¦ + 1) Hence we can write 1/(π¦ + 4)(π¦ + 1) =π΄/((π¦ + 4) )+π΅/((π¦ + 1) ) 1/(π¦ + 4)(π¦ + 1) =(π΄(π¦ + 1)+π΅(π¦ + 4))/(π¦ + 4)(π¦ + 1) Canceling denominators 1 = A(π¦+1)+B(π¦+4) Putting π=βπ 1= A (β1+1)+B(β1+4) 1= A Γ0+ B (3) 1=3B B =1/3 Putting π=βπ 1= A(β4+1)+ B(β4+4) 1= A(β3)+ B(0) 1=β3A A =(β1)/3 Therefore we can write 1/(π¦ + 4)(π¦ + 1) =π΄/((π¦ + 4) )+π΅/((π¦ + 1) ) 1/(π¦ + 4)(π¦ + 1) =(((β1)/( 3)))/((π¦ + 4) )+((1/3))/((π¦ + 1) ) Putting back π¦=π₯^2 1/(π₯^2 + 4)(π₯^2 + 1) =(((β1)/( 3)))/((π₯^2 + 4) )+((( 1)/( 3)))/((π₯^2+ 1) ) = (β1)/3(π₯^2 + 4) +1/3(π₯^(2 )+ 1) Integrating w.r.t. π₯ β«1ββ(1/(π₯^(2 )+ 4)(π₯^2 + 1) ππ₯) =β«1β((β1)/3(π₯^2 + 4) +1/3(π₯^2 + 1) )ππ₯ =β«1βγ(β1)/3(π₯^2 + 4) ππ₯+γ β«1βγ(β1)/3(π₯^2 + 1) ππ₯γ =(β1)/( 3) β«1βγ1/(π₯^2 + 2^2 ) ππ₯+1/3 β«1βγ1/(π₯^2 + 1^2 ) ππ₯γγ =(β1)/3 Γ 1/2 tan^(β1)β‘γπ₯/2+1/3 Γ 1/1 tan^(β1)β‘γπ₯/1+πΆγ γ =(β1)/( 6) tan^(β1)β‘γπ₯/2+1/3 tan^(β1)β‘γπ₯+πγ γ We know that β«1βγ1/(π₯^2 + π^2 ) ππ₯=1/π tan^(β1)β‘γπ₯/π+πγ γ =π/π γπππ§γ^(βπ)β‘γπβπ/π γπππ§γ^(βπ)β‘γπ/π+πγ γ